Threat Modeling Solution for Internet of Things in a Webbased Security Framework - Costa, Joana Cabral Amaral Nunes da (2022)
The Internet of Things (IoT) is a growing paradigm that provides daily life benefits for its users, motivating a fast paced deployment of IoT devices in sensitive scenarios. However, current IoT devices do not correctly apply or integrate security controls or technology, potentially leading to a wide panoply of problems, most of them with harmful impact to the user. Thus, this work proposes the development of a tool that helps developers create properly secure IoT devices by identifying possible weaknesses in the system. This tool consists of a module of a framework, denominated Security Advising Modules (SAM) in the scope of this work, and achieves the referred objective by identifying possible weaknesses found in the software and hardware of IoT devices. To define the weaknesses, a set of databases containing information about vulnerabilities and weaknesses found in a system were investigated throughout this project, and a restricted set of weaknesses to be presented was chosen. Since some databases contain hundreds of thousands of vulnerabilities, it was neither feasible nor pertinent to present them completely in the developed tool. Additionally, the questions to retrieve system information were identified in this work, allowing us to map the chosen weaknesses to the answers given by the developer to those questions. The tool developed was properly tested by running automated tests, with the Selenium framework, and also validated by security experts and evaluated by a set of 18 users. Finally, based on user feedback, it was concluded that the developed tool was useful, simple and straightforward to use, and that 89% of respondents had never interacted with a similar tool (adding, in this way, to the innovative character).